Bleomycin A6-loaded anionic liposomes with in situ gel as a new antitumoral drug delivery system. (2nd January 2016) - Ding, Weiming; Li, Yanfang; Hou, Xucheng; Li, Guiling
Abstract: The goal is to develop an in situ gel system comprising anionic liposomes (AL) containing bleomycin A6 (BLM A6) dispersed within the thermosensitive in situ gel for sustained release. The results indicated that the gelation temperature decreased due to AL within gel. Similarly, viscosity and mechanical parameters, such as gel strength for gel, could be enhanced by inducing lipid material with negative charge (phosphatidylglycerol) at 37 °C, which provided against corrosion at physiological condition. The in vitro release experiments performed with a dialysis method revealed that in situ gel with AL exhibited the longer drug-release period compared to that with or without nonionic liposomes. An in vivo fluorescence imaging study suggested that the gel with AL loading FITC-BLM A6 stayed in administration site at least for five days. A thermosensitive in situ gel with anionic liposome was a promising carrier for hydrophilic BLM A6, to be used in parenteral delivery system for anti-tumor treatment.